Exopolysaccharide from Trichoderma pseudokoningii induces macrophage activation. (20th September 2016) - Wang, Guodong; Zhu, Lei; Yu, Bo; Chen, Ke; Liu, Bo; Liu, Jun; Qin, Guozheng; Liu, Chunyan; Liu, Huixia; Chen, Kaoshan
Highlights: Exopolysaccharide (EPS) induces upregulation of NO, TNF-α, IL-1β and phagocytosis in RAW 264.7 cells. EPS activates macrophages through NF-κB and MAPKs signaling pathways. TLR4 and Dectin-1 receptors are involved in EPS-mediated activation of RAW 264.7 cells. Abstract: In this study, we evaluated the immunomodulatory activity of an exopolysaccharide (EPS) derived from Trichoderma pseudokoningii and investigated the molecular mechanism of EPS-mediated activation of macrophages. Results revealed that EPS could significantly induce the production of nitric oxide (NO), tumor necrosis factor (TNF)-α and interleukin (IL)-1β and enhance phagocytic activity in RAW 264.7 cells. Immunofluorescence staining indicated that EPS promoted the nuclear translocation of nuclear factor (NF)-κB p65 subunit. Western blot analysis showed that EPS increased the expression of inducible nitric oxide synthase (iNOS) protein, the degradation of IκB-α and the phosphorylation of mitogen-activated protein kinases (MAPKs). Furthermore, pretreatment of RAW 264.7 cells with specific inhibitors of NF-κB and MAPKs significantly attenuated EPS-induced TNF-α and IL-1β production. EPS also induced the inhibition of cytokine secretion by special antibodies against Toll-like receptor-4 (TLR4) and Dectin-1. These data suggest that EPS from Trichoderma pseudokoningii activates RAW 264.7 cells through NF-κB and MAPKs signaling pathways via TLR4 and Dectin-1.